Decomposição térmica de cascas de ovos para produção de cal a partir da concentração solar com lentes de Fresnel - Palhares, Dayana D´Arc de Fátima (2022)
Lime (CaO) is a very important material for the socioeconomic development of a country. This product has applications in agriculture, civil construction, steel and chemical industries in general, as well as in the environment for water treatment, disinfection, neutralization of gaseous pollutants, waste treatment and contaminated land. Alternatives to make the lime production process more sustainable can consist, among others, in the use of residues that are sources of calcium carbonate (CaCO3) and in the application of renewable energy sources, such as concentrated sunlight for energy supply required for the calcination reaction. Thus, this thesis had as its main objective the study of the calcination of eggshells (residues from the productive and consumer chain of laying poultry) with the use of a Fresnel lens solar concentrator. Through a phenomenological model, it was possible to predict the thermal equilibrium temperature and the heating time of the reactor to signal the feasibility of a commercial Fresnel lens to provide sufficient thermal energy for the aimed calcination reactions. In the conceived solar unit, the deviations for the temperature of thermal equilibrium were less than 7% in modulus, confirming, therefore, the reliability of the phenomenological model and the viability of the system to provide calcinations of eggshells. For this purpose, the eggshells were ground and separated into four particle size ranges [A (600-1000 μm), B (355-600 μm), C (212-355 μm) and D (125-212 μm)] and evaluated by many characterization techniques. The solar unit for the calcination reaction consisted of a 0.8971 m2 commercial Fresnel lens and a silicon carbide (SiC) reactor installed in the focal region of the refractive concentrator. In the solar unit, the calcination reaction conversions of CaCO3 present in eggshells were 43.15 to 86.05% for an experimental time of 20 min. The largest particle size range (600 to 1000 μm), a sample mass of 2.0 g and a temperature range of 876 to 896ºC were the operating conditions that maximized the conversion of eggshells into lime by the solar unit. Under these operating conditions, complete calcination of eggshells in lime was observed in experimental times equal to 30 min. The material resulting from the calcination was analyzed by X-Ray Diffraction (XRD) and only the phase corresponding to calcium oxide (CaO) was found. Thus, it was concluded that it was possible to produce lime by means of waste eggshells and with concentrated solar energy by a Fresnel lens.